A verified method for solving piecewise smooth initial value problems - Auer, Ekaterina; Kiel, Stefan; Rauh, Andreas (Zielona Góra: Uniwersytet Zielonogórski)
In many applications, there is a need to choose mathematical models that depend on non-smooth functions. The task of simulation becomes especially difficult if such functions appear on the right-hand side of an initial value problem. Moreover, solution processes from usual numerics are sensitive to roundoff errors so that verified analysis might be more useful if a guarantee of correctness is required or if the system model is influenced by uncertainty.
Keywords: interval methods; non-smooth systems; initial value problems